Indonesian Higher Education Institutions Competitiveness and Digital Transformation Initiatives - Priyanto, Panji; Suhandi, Ni Putu Mila (Jurnal Pendidikan Indonesia, 2022)
The COVID-19 pandemic is causing unexpected challenges for all education systems. Several online platforms launched by the Ministry of Education and Culture maximize available e-learning solutions and further develop lecturers' digital skills and competencies. This study aims to analyze the comparative needs of Indonesia's current digital higher education environment and conduct an in-depth study of digital learning in Indonesia's higher education environment. This study also outlines the mitigation plans, innovative strategies adopted, and implications and recommendations for universities in Indonesia. The research method uses discourse analysis with literature and news sources to assess the impact, challenges, and opportunities of higher education during the pandemic in Indonesia. This study found that the COVID-19 pandemic had a significant impact on higher education in Indonesia; Both lecturers and students at universities face many challenges in the teaching and learning process. The effect is worse in Eastern Indonesia due to poor internet connectivity for online learning. In terms of mitigating online learning, the impact is still unknown. The limitations of this study are that the literature and news studies are not comprehensive because the current pandemic crisis has not ended. This study can provide an overview of the limitations of a more empirical study that will be carried out on how the current crisis affects the learning process of higher education in Indonesia.